Effect of Modified Freezing Diluent on Post-Thaw Sperm Characteristics of Poor Freezable Sahiwal Bull - Sethi, Manisha; Shah, Nadeem; Mohanty, Tushar K; Bhakat, Mukesh; Yadav, Dileep K; Kumar, Pratyush; Kumar, Nishant (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
The study aimed to enhance the cryo-survivability and fertilization potential of poor freezable Sahiwal bull semen by devising a modified  extender and freezing protocol. This protocol incorporated a combination of trehalose and glycerol as cryoprotectants and freezing  with an aluminium block. The semen samples were split into three; the split 1 was extended in routine tris fructose egg yolk glycerol  (TFEG) extender and underwent the conventional vapour freezing (Control group). The other split samples considered as treatment  samples were extended with diluent having 75 % of TFEG and 25 % of trehalose (280 mOsm/l both) with glycerol percentage being 5, and  frozen using a conventional vapour freezing (T1) and modified freezing protocol with an aluminium block (T2). After freezing-thawing,  the progressive sperm motility, viability, HOS response and acrosome integrity were significantly (p ≤ 0.05) improved in treatment 2  compared to the control and treatment 1 groups. Along with this, the degree of oxidative stress (MDA production) was substantially  lower in treatment groups (T1 and T2) compared to control group. The results highlight the promising effectiveness of the modified  freezing method incorporating trehalose and glycerol as cryoprotectants and using an aluminium block. The significance of these  findings lies in the potential application of this technique for freezing-thawing semen, particularly from bulls with poor freezability.
Keywords: Bull; Glycerol; Modified freezing; Sperm; Trehalose